‘It is an emotional rollercoaster!!!’ Experiences of mothers of preterm newborns seeking care at a tertiary hospital in Ghana: a qualitative phenomenological study - Ruth Nimota Nukpezah; Gideon Awenabisa Atanuriba (BMJ Open)
Objective To describe, through the phenomenological lens, the experiences of mothers following preterm birth and admitted at a tertiary hospital.Methods Design Descriptive phenomenological study.Setting Neonatal intensive care unit (NICU) of a tertiary hospital in Ghana.Population Mothers who delivered prematurely and were admitted.Main outcome measures Experiences of mothers who delivered prematurely and had their neonates admitted to the NICU.Results Four themes and three subthemes were realised: (1) maternal anxiety about unknown outcomes of the newborn condition, (2) the positive impact of family-centred care, (3) maternal roles for preterm care and (4) poor support for maternal involvement in care.Conclusions Mothers of preterm newborns sustained varying degrees of emotional trauma and faced challenges that deprived them of active involvement in their newborn care. Despite these, family-centred care was impactful and gave a window of opportunity for mothers to provide maternal roles. We highly recommend tailored emotional and psychological supports for mothers who have delivered prematurely, as it is crucial to ensuring both maternal and neonatal survival.